Communication, Accommodation, and Employee Responsiveness at PT Global Event Organizer - Dwie Maharany; Sri Wulandari; Dian Andriany (Siber Nusantara Research, 2026)
The role of communication as a catalyst enhancing the performance of work groups is especially noticeable in the event organizer industry, which functions with a rapid click and involves numerous stakeholders. The issues in this research include communication accommodation and employee responsiveness that occur in work groups PT Global Event Organizer, as well as barriers to communication at work the process in PT Global Event Organizer. This study is important in that it aims to develop a deeper understanding of communication accommodation practices, responsiveness, and the consequences these have on work group effectiveness. This study uses a qualitative approach by a case study method. Data were collected through in-depth interviews, observation, and documentation, with the General Manager as the key informant and employees as supporting informants. The results of this study show that, in terms of communication accommodation, employees at PT Global Event Organizer consistently adjust their communication styles, use language that is easy to understand, and maintain attitudes of mutual respect. In terms of responsiveness, employees demonstrate responsiveness through caring attitudes, refraining from blaming others, and providing support. These adaptive and responsive communication practices help minimize miscommunication, strengthen togetherness, and support the smooth functioning of teamwork.